High-riding innominate artery in the neck – a hazardous presentation during surgery - Akhtar, Sareema Eman; Shakil, Saad; Dhanani, Rahim; Wasif, Muhammad (Journal of the Pakistan Medical Association, 2023)
Aberrant innominate artery lying high in the neck is a rare entity that can be encountered intraoperatively during midline neck surgeries such as thyroidectomy and tracheostomy. Surgeons should be mindful of this entity as injury to the artery can lead to life-threatening haemorrhage. We report a case of a 40 year old female in whom an aberrant innominate artery was identified high in the neck, while performing a total thyroidectomy. Keywords: Aberrant innominate artery, Thyroidectomy, Tracheostomy, Aorta.